2007
DOI: 10.1590/s0034-89102007000300009
|View full text |Cite
|
Sign up to set email alerts
|

Luz e galinhas como fatores de atração de Nyssomyia whitmani em ambiente rural, Paraná, Brasil

Abstract: Light and hens as attraction factors of Nyssomyia whitmani in a rural area, Southern Brazil ABSTRACT OBJECTIVE: To verify the infl uence of traps with electric light and hens as factors that attract sandfl ies and compare results between capture methods. METHODS:The study was conducted in the Palmital Farm, Southern Brazil. Sandfl y collections were conducted with Falcão traps and an electric aspirator, fortnightly, between 8 p.m. and 11 p.m. in the presence or absence of light and hens in peridomiciliary area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 10 publications
2
17
0
4
Order By: Relevance
“…The published literature also shows that chickens attract sand flies [4346]. Chicken coops and pigpens are recognized as resting places for adults of both sexes, where females also take their blood meals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The published literature also shows that chickens attract sand flies [4346]. Chicken coops and pigpens are recognized as resting places for adults of both sexes, where females also take their blood meals.…”
Section: Discussionmentioning
confidence: 99%
“…Further, these ecotopes provide shade, moisture and soil with organic matter providing suitable conditions for breeding sites of the immature flies [4749]. Teodoro et al [46] showed that twice the number of sand flies (testing 8 species) could be captured in environments containing chickens compared to those without. Ximenes et al [50] showed that the presence of domesticated animals and low cleanliness of local conditions help maintain high population densities of sand flies.…”
Section: Discussionmentioning
confidence: 99%
“…When working with eight different species of these flies, Teodoro et al (2007) captured twice as many individuals in the presence of chickens. According to Ximenes et al (1999), the presence of domestic animals associated with poor cleaning conditions contributes to the maintenance of high abundance of Lu.…”
Section: Discussionmentioning
confidence: 99%
“…Os mesmos autores 12 sugeriram que possivelmente esses insetos sejam capazes de lembrar dos locais de agregação. Embora se saiba que flebotomíneos de ambos os sexos sejam atraídos pela luz 26 , pode-se inferir com base nas observações de gibson e Torr 9 que este estímulo tem importância secundária para a localização do hospedeiro, devido à baixa percepção visual dos dípteros hematófagos.…”
Section: Discussionunclassified